Immediate Implant Placement in Infected Sites: A Case Series. Issue 2 (1st February 2013) - Marconcini, Simone; Barone, Antonio; Gelpi, Federico; Briguglio, Francesco; Covani, Ugo
Abstract : Background: Immediate implant placement has several advantages, such as reduction in the number of surgical treatments and reduction of the time between tooth extraction and the placement of the definitive prosthesis. However, there are still some situations that could jeopardize the success of the aforesaid therapy, such as the presence of an infection caused by periodontal disease or periapical lesions. The aim of this case series is to evaluate the clinical success of implants placed in fresh extraction sockets that showed clinical signs of periodontal disease. Methods: Thirteen patients (six males and seven females, 24 to 65 years old) are included in this case series. After initial examination and treatment planning, all patients underwent the periodontal treatment deemed necessary to facilitate wound healing. Twenty teeth were extracted as a result of an infection. Second‐stage surgery was performed 4 months after the initial procedure. The following clinical parameters were evaluated for each patient at the time of implant placement and at the end of the 12‐month follow‐up period: 1) clinical attachment level (CAL); 2) presence or absence of mobility; 3) presence or absence of pain; and 4) presence or absence of suppuration. The bone level was measured as the distance from the implant shoulder to the first bone–implant contact (distance bone–implant [DIB]) by periapical radiographs. The stability and health of the soft tissue were clinically evaluated by means of the plaque score. Results: The healing period was uneventful for all the patients. All the implants were osseointegrated. At the end of the 12‐month follow‐up period, patients were asymptomatic and showed no signs of infection or bleeding when probed. The mean CAL at the mid‐buccal location per implant was 0.8 mm at baseline and 0.9 mm at the end of the follow‐up. The mean width of keratinized mucosa measured at the mid‐buccal location per implant at baseline and 1‐year visits was 3.2 ± 0.4 mm and 3.3 ± 0.5 mm, respectively. The periapical radiographs, obtained in a standardized manner, revealed a mean increase of 0.5 mm in the DIB value. At the 12‐month follow‐up, the presence of plaque was observed in 44 of the 80 sites analyzed. Conclusion: Based on the results of this case series, placement of implants in fresh extraction sockets affected by infection may be a valid operative technique that leads to predictable results if adequate preoperative and postoperative care is taken.